An extended chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids phenotype. (25th June 2014) - Lane, Chris; Phadke, Rahul; Howard, Robin
Abstract : Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) is a recently described central nervous system inflammatory condition. In this case report we describe a patient initially with features consistent with this syndrome, who represented with seizures (not previously reported in this syndrome) and corresponding prominent cortical involvement on imaging (also not previously noted). Owing to diagnostic uncertainty, cerebral biopsy was performed revealing histology consistent with CLIPPERS, excluding other differentials. Following a further brainstem relapse, this patient was treated with high-dose steroids, subsequently switched to a tapering oral regime and now, azathioprine, a steroid-sparing agent. She remains well on this.